EMF treatment delays mesenchymal stem cells senescence during long-term in vitro expansion by modulating autophagy - Cai, Wenxiang; Xiao, Yifan; Yan, Jiyuan; Peng, Hao; Tu, Chang (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Bone marrow mesenchymal stem cells (BMSCs) are widely used in tissue engineering and regenerative medicine as seed cells. Due to low amount in bone marrow, BMSCs must be expanded and cultured in vitro before application. However, the senescence of stem cell caused by long-term in vitro culture greatly limits its efficacy of transplantation.In this study, we propose an approach based on electromagnetic fields (EMF) treatment to rejuvenate aged BMSCs due to long-term in vitro culture. Aged BMSCs were treated with sinusoidal EMF (50Hz, 0.4mT), and stem cell senescence, cell proliferation, cell differentiation, cell stemness and autophagy level were detected.Additionally, aged BMSCs-laden hydrogels were transplanted into the rat critical-sized calvarial defect with or without EMF treatment. The bone formation was evaluated 8 weeks after surgery.Our results indicated that the BMSCs age significantly after long-term in vitro passaging. The self-renew, multiple differentiation capacity, senescence phenotypes and stemness of aged BMSCs are partly reversed by EMF treatment with a frequency of 50 Hz and strength of 0.4 mT. Moreover, declined autophagy level is observed in BMSCs during long-term in vitro passaging and BMSCs senescence is closely associated with autophagy regulation. Additionally, the mechanistic investigation reveals that EMF treatment rejuvenate senescent BMSCs by enhancing autophagy.Furthermore, EMF treatment significantly promote the therapeutic effect of long-term passaged BMSCs on bone formation in vivo.Overall, our study identifies a practical approach for the rejuvenation of old BMSCs and may provide a promising candidate in tissue engineering and stem cell therapy.